KEBARADAAN LAYANAN BIMBINGAN DAN KONSELING DI MASA PANDEMI COVID 19 - I Wayan Juliawan; Pande Wayan Bawa; Dewa Gede Eka Sastra Wiguna; Kadek Suhardita (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The study was conducted to find out about the existence of guidance and counseling services during the COVID-19 pandemic. This study focuses on how BK teachers deal with students in adjusting and what guidance is provided during the COVID-19 pandemic. This research uses quantitative research with survey method. This study was conducted to find out how important BK teachers are in providing guidance and counseling services to students during the pandemic. The researcher used a sample of seven schools in Kediri tabanan which consisted of two high schools and five junior high schools, with 36 respondents as a number of students and of them there were 6 students who conducted a direct survey with the researcher. The conclusion of this study is that students need online counseling services, especially in the field of interests and talents, and the role of guidance and counseling teachers at this time is very important.